Factors associated with vertical transmission of syphilis in a city in the State of São Paulo - Serra Santana , Natália Caroline (2023)
Background and Objectives: Syphilis is a sexually transmitted infection with low-cost and accessible treatment; however, it is considered a public health problem. Further studies are needed to improve knowledge about the factors that may contribute to the mother-to-child transmission of syphilis. Given its high detection rate in pregnant women and the possible adverse events of syphilis in Brazil, the objective was to evaluate the association of individual and clinical characteristics of syphilis with the incidence of congenital syphilis in pregnant women. Methods: This retrospective study was performed in a medium-size municipality in the State of São Paulo. Notification forms from the Notifiable Diseases Information System were used and the occurrence of congenital syphilis was the outcome of the study. Bivariate analyses and logistic regression were performed with variables that obtained p values <0.25. Results: Most pregnant women were 20-34 years old (62.2%) and had white skin (63.2%) and incomplete elementary schooling (35.4%). The occurrence of congenital syphilis was associated with the maternal syphilis diagnosis (p<0,001) and with not performing the treponemal test during the prenatal examination (p =0.014). There was a greater risk for the occurrence of congenital syphilis in cases with late diagnosis during pregnancy (OR=16.48; 95%CI 3.22-84.26) and tertiary/latent clinical classification (OR=7.62; 95%CI 1.40-41.54). Conclusion: Maternal diagnosis in the third trimester of pregnancy and tertiary/latent clinical classification were the main risk factors for the occurrence of congenital syphilis, reinforcing the importance of a quality prenatal examination performed timely.